Upadacitinib as Novel Treatment for Rheumatoid Arthritis with T-Cell Granular Lymphocytic Leukemia: A Case Report and Narrative Review - Young Min Cho; Erik W. Anderson; Sara Guevara; Santiago J. Miyara; Aqsa Iqbal; Judith Aronsohn; Ernesto P. Molmenti; James M. Mumford; Barbara Keber; Farideh Zonouzi-Zadeh; Yousoun Ha; Petros G. Nikolinakos; et al. (Journal of Clinical Rheumatology and Immunology, 2022)
T-cell large granular lymphocyte (T-LGL) leukemia is a rare and indolent clonal disorder of LGLs, associated with rheumatoid arthritis and neutropenia. The authors present a case of a 62-year-old male with rheumatoid arthritis (RA) who was diagnosed with T-LGL leukemia, with predominant neutropenia, and a poor response to conventional treatment. Subsequently, tofacitinib (a Janus Kinase 1 and 3 inhibitor, [JAK1/3 inhibitor]) resulted in improvement of the patient’s RA symptoms and temporary improvement of the neutropenia. Ultimately, upadacitinib (a specific JAK1 inhibitor) resulted in further improvement of the neutropenia and control of his RA. To the best of our knowledge, this is the first case report of coexisting RA and LGL leukemia that was treated with upadacitinib and showed clinical improvement.